Is America Unrivaled? A Repeated Game Analysis - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
I use a strategic setup to investigate whether unipolarism can indeed persist as a long run equilibrium. In a three-country world, a global power may subsidise two satellites so as to incentivate them not to invest to build up a coalition against it. I single out the conditions under which the one-shot game is a Prisoners' Dilemma where no subsidy is paid and the coalition arises at equilibrium. Then, I revert to the infinitely repeated game and apply the Perfect Folk Theorem to characterise the critical thresholds of discount factor sustaining unipolarism at the subgame perfect equilibrium.
Keywords: 330; Geoökonomie; Gefangenendilemma; Wiederholte Spiele